2011
DOI: 10.1029/2011ja016876
|View full text |Cite
|
Sign up to set email alerts
|

Multievent study of the correlation between pulsating aurora and whistler mode chorus emissions

Abstract: [1] A multievent study was performed using conjugate measurements of the Time History of Events and Macroscale Interactions during Substorms (THEMIS) spacecraft and an all-sky imager during periods of intense lower-band chorus waves. The thirteen identified cases support our previous finding, based on two events, that the intensity modulation of lower-band chorus near the magnetic equator is highly correlated with quasiperiodic pulsating auroral emissions near the spacecraft's magnetic footprint, indicating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
136
5
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(157 citation statements)
references
References 40 publications
15
136
5
1
Order By: Relevance
“…The 4-Hz modulation, which is related to the spacing of chorus elements, is concentrated at the lower-latitude edge of the auroral patch. However, the observed high correlation region is distributed only around the edge region of the auroral patch with almost the same time difference value of À0.26 s, in contrast to the findings of a previous study (Nishimura et al, 2010(Nishimura et al, , 2011) that used a low temporal resolution (3 s) data set obtained by the THEMIS all-sky imagers (Mende et al, 2008). The observed chorus waves could be in the nonducted mode, because the associated chorus waves were not observed at the ground station at Chistochina (40 km east of Gakona).…”
Section: Figures 2a and 2bcontrasting
confidence: 99%
See 1 more Smart Citation
“…The 4-Hz modulation, which is related to the spacing of chorus elements, is concentrated at the lower-latitude edge of the auroral patch. However, the observed high correlation region is distributed only around the edge region of the auroral patch with almost the same time difference value of À0.26 s, in contrast to the findings of a previous study (Nishimura et al, 2010(Nishimura et al, , 2011) that used a low temporal resolution (3 s) data set obtained by the THEMIS all-sky imagers (Mende et al, 2008). The observed chorus waves could be in the nonducted mode, because the associated chorus waves were not observed at the ground station at Chistochina (40 km east of Gakona).…”
Section: Figures 2a and 2bcontrasting
confidence: 99%
“…A coordinated geomagnetic conjugate observation could be performed for each of Arase's elliptic orbits. The data set of Arase and PWING have better sensitivities and higher temporal resolutions for waves and aurora measurements than constellation observations by the Time History of Events and Macroscale Interactions during Substorms (THEMIS) satellites and the THEMIS Ground Based Observatory (GBO) (Nishimura et al, 2010(Nishimura et al, , 2011. The data set of Arase and PWING have better sensitivities and higher temporal resolutions for waves and aurora measurements than constellation observations by the Time History of Events and Macroscale Interactions during Substorms (THEMIS) satellites and the THEMIS Ground Based Observatory (GBO) (Nishimura et al, 2010(Nishimura et al, , 2011.…”
Section: Microscopic Observations Of Pulsating Auroramentioning
confidence: 99%
“…It is worth noting that the resulting minimum timescales of 20 s to 60 s for 15 keV to 100 keV electrons are similar to the observed (16) as a function of the electron density N e at L = 4.5 for E = 1 MeV, with the same other parameters as in Figure 4, and the scaling N e 7/9 from equation (19) (dashed line) and the full numerical results (red diamonds). periods of pulsating auroras, which were recently shown to be highly correlated with lower-band chorus [Nishimura et al, 2011]. These timescales are also similar to, or lower than strong diffusion timescales of isotropization t sd $ 1.8LR E g/ (pca LC 2 ), where R E is the Earth's radius [Lyons, 1973;Schulz, 1974].…”
Section: Comparisons With Full Numerical Simulations and Discussionmentioning
confidence: 71%
“…In particular, an important population of plasma sheet low-energy electrons (E $ 10 À 100 keV) are injected near midnight in the outer belt during storms or substorms. Drifting from midnight through dawn to noon, such low-energy electrons are believed to excite lower-band chorus waves near the equator through thermal anisotropy or loss cone instability at small pitch angles, the generated quasi-parallel whistler waves in turn accelerating some electrons to relativistic energies at large pitch angles in the night sector and scattering particles into the loss cone at small pitch angles on the dawnside, finally leading to precipitations in the atmosphere and pulsating auroras Li et al, 2007;Summers et al, 2007b;Ni et al, 2008;Nishimura et al, 2011]. The inferred timescales for precipitation range from hours to days during periods of storm-enhanced convection Li et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been rare to observe equatorial and auroral regions simultaneously and to precisely treat magnetic field line modeling, recent studies by Nishimura et al [2010Nishimura et al [ , 2011 determined magnetic field mapping and identified uniquely that lower band chorus is responsible for driving pulsating aurora. Thus, the study of chorus intensity modulation has a direct impact on understanding the driver of auroral pulsation.…”
Section: Introductionmentioning
confidence: 99%